2015
DOI: 10.15835/nsb719478
|View full text |Cite
|
Sign up to set email alerts
|

MtDNA Barcode Identification of Finfish Larvae from Vellar Estuary, Tamilnadu, India

Abstract: Planktonic larvae were captured in the shallow Vellar estuary, Tamilnadu, India, during January to June 2013 using zooplankton net. Larvae were identified to the species level by comparison with Genbank data base using MtDNA sequence data. Further analysis showed that there is no sequence variation within-species, whereas between-species variation was more than 25%, supporting the suitability for species identification. The highest genetic distance was observed between A. nigropunctatus and M. cephalus (0.434)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…The low genetic distance of 0.002 was reported by Nuryanto et al (2017) on two morphotypes larvae, which was suggested to belong to single species. Additional earlier studies also proved that individuals from single species had low genetic distances (Thirumaraiselvi et al, 2015;Hubert et al, 2012), even among conspecific specimens collected from geographically separated populations (Sachithanandam et al, 2012). Higher genetic distance among individuals from single species was reported in other groups of animals, such as in thrips (Kurniawaty et al, 2016), andin Lepidoptera (deWaard et al, 2011).…”
Section: Resultsmentioning
confidence: 82%
“…The low genetic distance of 0.002 was reported by Nuryanto et al (2017) on two morphotypes larvae, which was suggested to belong to single species. Additional earlier studies also proved that individuals from single species had low genetic distances (Thirumaraiselvi et al, 2015;Hubert et al, 2012), even among conspecific specimens collected from geographically separated populations (Sachithanandam et al, 2012). Higher genetic distance among individuals from single species was reported in other groups of animals, such as in thrips (Kurniawaty et al, 2016), andin Lepidoptera (deWaard et al, 2011).…”
Section: Resultsmentioning
confidence: 82%